Artistic interpretation of the mythonyms of Angel and Devil in the works of A.Navoi: Middle European scientific bulletin ISSN 2694-9970. VOLUME 5, OCTOBER 2020. – pp 128-131. - Rajabova, Marifat (FILOLOGIYA UFQLARI JURNALI, 2023)
Maqolada adabiyot shinoslikmasalari tahlil va taqdit qilingan